Apolipoprotein H, a new mediator in the inflammatory changes ensuing in jeopardised human myocardium. Issue 11 (1st November 2000) - Niessen, H W M; Lagrand, W K; Rensink, H J A M; Meijer, Ch J L M; Aarden, L; Hack, C E
Abstract : Aim —To investigate the presence of membrane "flip flop" in ischaemic human myocardium, we assessed depositions of apolipoprotein H (apoH; β2-glycoprotein 1) in ischaemic myocardium. Serum protein apoH can bind to negatively charged phospholipids and can also inhibit blood coagulation in vitro. We hypothesised that, because of its affinity for phosphatidyl serine, apoH might bind to "flip flopped" cells and would therefore be useful as a marker for membrane flip flop in vivo. Methods —Myocardial tissue specimens were obtained from patients who had died within 14 days of acute myocardial infarction. Results —Immunohistochemical analysis of these specimens revealed that apoH was selectively deposited in infarcted areas of human myocardium of at least one day's duration. Depositions of apoH were not found in non-ischaemic myocardial tissue samples obtained from patients who died from other (extracardial) causes. In vitro experiments with the human leukaemia T cell line Jurkat, subjected to apoptosis by etoposide, showed that apoH was bound to the membrane of apoptotic cells. However, these experiments also indicated that flip flop itself is not sufficient for apoH binding. In addition, Jurkat cells that bound apoH were positive for activated complement complexes, as was also found in the human heart. Conclusions —These results suggest that apoH is involved in the inflammatory processes that occur in ischaemic myocardium.